Bidirectional boost/buck quadratic converter for distributed generation systems with electrochemical storage systems - Pires, V. Fernão (2018)
The increasing number of distributed generation systems using renewable and non-conventional energy sources show the trend of future generation systems. Most of these systems require power electronic converters as an interface between the DC voltage buses and electrochemical storage systems. Such storage systems, like batteries or supercapacitors, usually need bidirectional DC-DC converters to allow their charge or discharge according with necessary operation conditions. In this paper, a non-isolated bidirectional Buck-Boost converter with high voltage gain for electrochemical storage devices used in distributed generation systems is presented. To achieve high voltage gain ratios, the proposed topology presents quadratic characteristics in both step-down (Buck) and step-up (Boost) operation modes. In addition to the wide conversion range, it presents continuous input and output current, reduced charging/discharging ripple and simple control circuitry. All these features allow the energy exchange smoothly and continuously resulting in a longer durability of storage devices. The principle of the operation of the proposed converter in both operation modes, as well as their theoretical analysis will be discussed. The performance of this bidirectional power converter is confirmed through simulation and experimental results.